A Prospective Study of Lymphatic Filariasis in an Endemic Village of Kapilbastu District, Nepal - Gupta, R.; Lanichhane, J. (Ecoprint: An International Journal of Ecology, 2009)
Lymphatic filariasis is a major problems health problem in Nepal. A prospective study was conducted in Maharajgunj VDC, Kapilbastu district, Nepal with the objective to analyze the epidemiological situation of the disease lymphatic filariasis. A total of 505 blood samples were collected by ear-lobe prick method. Out of 505 blood samples, 50 samples (9.90%) were found to be positive for microfilaria (mf) within age between 3 to 85 years. In the present study the highest endemicity rate was found in the age group 61-70 years and the lowest endemicity rate 6.67% was found in the age group < = 10 years. Illiteracy, poor sanitation , lack of knowledge about the disease and not taking precaution of filariasis , habit of working in the fields till late night and early in the morning, sleeping outdoor without bed-nets, keeping cattle in the same house where they live were identified as risk factors for the disease. Key words: Prevalence; Lymphatic filariasis; Microfilaria; Crude disease rate. doi: 10.3126/eco.v13i0.1626 Ecoprint (An International Journal of Ecology) Vol. 13, No. 1, 2006 Page: 29-34